1973
DOI: 10.2466/pms.1973.36.1.311
|View full text |Cite
|
Sign up to set email alerts
|

Personality Characteristics of Creative Women

Abstract: Women authors who were listed in Who's Who in America, and women artists in Who's Who in American Women responded to the Sixteen Personality Factor Questionnaire. Both groups were found to be more aloof, intelligent, emotional, aggressive, adventurous, imaginative, radical, and self-sufficient, and less group-dependent and controlled than women in the general population. Although the women artists did not score beyond the average on sensitivity and self-control, the authors were more sensitive and less control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

1978
1978
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 14 publications
0
13
0
2
Order By: Relevance
“…STUDIES OF CREATIVE WOMEN Studies and reviews of creative women focused on women engaged in art (Nochlin 1971(Nochlin , 1979Greer, 1979); writing (Olsen 1970(Olsen , 1978Spacks 1972;Showalter 1971;Helson 1973b); art and literature (Anastasi & Schaefer 1969;Schaefer 1969aSchaefer ,b, 1970bSchaefer , 1971bSchaefer , 1972bSchaefer ,c, 1973Bachtold & Werner 1973); science (Walberg 1969b;Bach told & Werner 1972); mathematics (Helson 197 1); psychology (Bachtold & Werner 1970); elementary school teaching (Torrance, Tan & Allman 1970); college teaching (Groth 1975); and other assorted activities (Helson 1966a(Helson ,b, 1967a(Helson , 1968bTorrance 1972a;Suter & Domino 1975;Yu 1977;Blaubergs 1978;Morse & Bruch 1978;Lemkau 1979). It is clear that those wishing to examine the psychology of creative women have far more empiri cal evidence to look at today than they did 15 years ago.…”
Section: Creativity In Me N and Wo Men: A Ne W Focus On Sex-related Dmentioning
confidence: 99%
See 2 more Smart Citations
“…STUDIES OF CREATIVE WOMEN Studies and reviews of creative women focused on women engaged in art (Nochlin 1971(Nochlin , 1979Greer, 1979); writing (Olsen 1970(Olsen , 1978Spacks 1972;Showalter 1971;Helson 1973b); art and literature (Anastasi & Schaefer 1969;Schaefer 1969aSchaefer ,b, 1970bSchaefer , 1971bSchaefer , 1972bSchaefer ,c, 1973Bachtold & Werner 1973); science (Walberg 1969b;Bach told & Werner 1972); mathematics (Helson 197 1); psychology (Bachtold & Werner 1970); elementary school teaching (Torrance, Tan & Allman 1970); college teaching (Groth 1975); and other assorted activities (Helson 1966a(Helson ,b, 1967a(Helson , 1968bTorrance 1972a;Suter & Domino 1975;Yu 1977;Blaubergs 1978;Morse & Bruch 1978;Lemkau 1979). It is clear that those wishing to examine the psychology of creative women have far more empiri cal evidence to look at today than they did 15 years ago.…”
Section: Creativity In Me N and Wo Men: A Ne W Focus On Sex-related Dmentioning
confidence: 99%
“…Studies of creative adult artists, scientists, mathematicians, and writers find them scoring very high on tests of general intelligence (e.g. Barron 1969;Bachtold & Werner 1970;Helson & Crutch field 1970b;Cattell 1971;Helson 1971;Bachtold & Werner 1973;Gough 1976a), though rs between tested intelligence and creative achievement in these samples range from insignificantly negative (r = -.05, Gough 1976a) to mildly and significantly positive (r = +'31, Helson 1971 Milgram, Yitzhak & N. A. Milgram 1977;Frederiksen & Ward 1978;and Hocevar 1980) and sometimes modestly positive (e.g. McDermid 1965;Helson 1971;Vernon 1972b;Torrance 1972b;Schmidt 1973;Kogan & Pankove 1974;Gough 1976a;and Hocevar 1980).…”
Section: Creativity and Traditional Measures Of Intelligencementioning
confidence: 99%
See 1 more Smart Citation
“…The dropouts were perhaps lacking in discipline or seeking immediate gratification. Bachtold and Werner (1973) attempted to detect personality traits of women authors and artists who were listed in Who's Who in America. Citing the lack of in depth studies of women up to that time, Bachtold and Werner investigated 273 female authors and 254 artists.…”
Section: New Domains In Creativitymentioning
confidence: 99%
“…Several previous investigations of the creative personality (Amos, 1978;Bachtold & Werner, 1973;Cross, Cattell, & Butcher, 1967;Gotz & Gotz, 1979) uncovered characteristics that differed significantly between artists and nonartists. Cross et al (1967), for example, used Cattell's 16PF test and found that 10 personality factors discriminate artists from controls (lecturers and students of both sexes).…”
mentioning
confidence: 97%